Trimesic acid dimethyl sulfoxide solvate: space group revision - Bernès, Sylvain; Hernández, Guadalupe; Portillo, Roberto; Gutiérrez, René (International Union of Crystallography, 2008)
The structure of the title solvate, C9H6O6C2H6OS, was determined 30 years ago [Herbstein, Kapon & Wasserman (1978). Acta Cryst. B34, 1613–1617], with data collected at room temperature, and refined in the space group P21. The present redetermination, based on high-resolution diffraction data, shows that the actual space group is more likely to be P21/m. The crystal structure contains layers of trimesic acid molecules lying on mirror planes. A mirror plane also passes through the S and O atoms of the solvent molecule. The molecules in each layer are interconnected through strong O—HO hydrogen bonds, forming a two-dimensional supramolecular network within each layer. The donor groups are the hydroxyls of the trimesic acid molecules, while the acceptors are the carbonyl or the sulfoxide O atoms.